Analisis Program Infaq Siswa terhadap Pembentukan Nilai-Nilai Karakter Peserta Didik - Muhamad Togar Sastra Yusup; Jajang Rustandi; Mirta Anthoni (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aimed to analyze the influence of the 3S Charity Program (Sehari Seribu Saja-One Thousand Rupiah a Day) on the development of students' character values at MA Al-Azhar Center Baturaja. The study employed a quantitative approach with a correlational research design. The population consisted of 340 students, while 77 respondents were selected using the Slovin formula through a stratified random sampling technique. Data were collected through questionnaires, observations, interviews, and documentation. The data were analyzed using descriptive statistics and simple linear regression. The findings indicated that the implementation of the 3S Charity Program was categorized as moderate (61%), while students' character development was also categorized as moderate (61%). Regression analysis revealed a positive and significant effect of the 3S Charity Program on students' character development, with a correlation coefficient of 0.485 and a coefficient of determination of 23%. The resulting regression equation was Y = 31.894 + 0.524X, indicating that improvements in the implementation of the 3S Charity Program were followed by improvements in students' character development. Therefore, the 3S Charity Program can serve as an effective habituation strategy for fostering social awareness, responsibility, and sharing attitudes among students within the school environment.